A Broadband P-Shaped Circularly Polarized Monopole Antenna With A Single Parasitic Strip - Zakaria, Zahriladha; Alsariera, Hussein Salameh Mahmoud; Awang Md Isa, Azmi (IEEE, 2019)
A new broadband circular polarization (CP) monopole antenna with simple structure is proposed. The antenna consists of a P-shaped monopole and modified ground plane with rectangular stub, and results demonstrated that the 10 dB impedance bandwidth (ZBW) is 118.5% (1.6–6.25 GHz) and the 3 dB axial-ratio bandwidth (ARBW) is 104.4% (1.9–6.05 GHz). Procedures to improve the proposed antenna design and the CP mechanism analysis were performed. The performance of different parameters is presented. The advantages of the proposed antenna are broader ZBW and ARBW, simpler structure, and compact size.